St. Thomas, Divine Freedom, and Compatibilism: A Reply to Pedersen and Lilley - Chopp, Joel Thomas (Journal of reformed theology, 2025)
In their recent article, Daniel J. Pedersen and Christopher Lilley construct a two-pronged response to the modal collapse argument against divine simplicity. The first prong relies heavily on distinctions developed by Thomas Aquinas. This essay contests their interpretation of Aquinas by demonstrating that they misconstrue fundamental elements of his modal semantics and doctrine of divine freedom. Subsequently, for theologians who adopt a Thomistic account of these doctrines, it cannot provide a means for avoiding the modal collapse argument. I conclude with suggestions for fruitful avenues to pursue in the ongoing debate over the doctrines of divine simplicity and freedom.